2009
DOI: 10.1158/0008-5472.sabcs-09-803
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Blind, Randomized, Placebo-Controlled Trial of High Dose Vitamin D Therapy on Musculoskeletal Pain and Bone Mineral Density in Anastrozole-Treated Breast Cancer Patients with Marginal Vitamin D Status.

Abstract: Rationale: Musculoskeletal (MS)pain is a known adverse class effect of aromatase inhibitors. Previously we reported high prevalence of Vitamin D deficiency in breast cancer patients complaining of MS pain, and anecdotal improvement of MS pain with weekly supplementation of high dose Vitamin D (HDD) (1). Here we report on a randomized double-blind, placebo-controlled trial of weekly HDD (ergocalciferol 50,000 IU) versus placebo (PBO) in breast cancer patient receiving anastrozole, with new or worsening MS pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The authors concluded that monitoring serum vitamin D levels is important in reducing musculoskeletal pain. Moreover, a 6-month randomized trial in patients with breast cancer and low vitamin D levels (10-29 ng/ml; N = 60) showed that after 2 months of anastrozole treatment and weekly vitamin D at 50,000 IU, there was improved musculoskeletal pain compared with placebo [66]. Oral dosing of vitamin D 50,000 IU once a week for 8 weeks is typically sufficient to treat vitamin D deficiency [63].…”
Section: Recommendationsmentioning
confidence: 99%
“…The authors concluded that monitoring serum vitamin D levels is important in reducing musculoskeletal pain. Moreover, a 6-month randomized trial in patients with breast cancer and low vitamin D levels (10-29 ng/ml; N = 60) showed that after 2 months of anastrozole treatment and weekly vitamin D at 50,000 IU, there was improved musculoskeletal pain compared with placebo [66]. Oral dosing of vitamin D 50,000 IU once a week for 8 weeks is typically sufficient to treat vitamin D deficiency [63].…”
Section: Recommendationsmentioning
confidence: 99%
“…BCS on AI therapy often experience musculoskeletal symptoms, and these musculoskeletal symptoms may be related to low levels of vitamin D 2,3…”
Section: Introductionmentioning
confidence: 99%